2019
DOI: 10.1039/c9ta05948b
|View full text |Cite
|
Sign up to set email alerts
|

Two-step growth of CsPbI3−xBrx films employing dynamic CsBr treatment: toward all-inorganic perovskite photovoltaics with enhanced stability

Abstract: The dynamic CsBr treatment on α-CsPbI3 significantly improves the power conversion efficiency, reproducibility, and stability of all-inorganic CsPbI3−xBrx perovskite solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 44 publications
2
34
0
Order By: Relevance
“…When including the SOC effect in PBE-GGA and HSE [18] for CsPbI 3 , ref. [41] for CsPbI 3−x Br x (x = 0.66), ref. [38,39] for CsPbIBr 2 and ref.…”
Section: Electronic and Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…When including the SOC effect in PBE-GGA and HSE [18] for CsPbI 3 , ref. [41] for CsPbI 3−x Br x (x = 0.66), ref. [38,39] for CsPbIBr 2 and ref.…”
Section: Electronic and Optical Propertiesmentioning
confidence: 99%
“…It should be noted that during the anion exchange their solid solutions CsPb(Br x I 1-x ) 3 are not excluded to form, especially in thicker film. Rather, to avoid the phase degradation of CsPbI 3 under ambient conditions, many researchers preferred to develop bromide-based PSCs such as CsPbBr 3 (efficiency, 8.8%) [33,34,35], CsPbIBr 2 (9.8%) [36,37,38,39], CsPbI 2 Br (16.1%) [40] and CsPb(Br x I 1-x ) 3 (x = 0.66, 14.1%) [41,42,43,44]. In spite of such intensive experimental studies, theoretical works are yet absent and thus a persuasive explanation for halide anion exchange is not provided.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most commonly studied 3D perovskites, MAPbI 3 , degrades under thermal stress due to the highly volatile MA+ ion [ 1 ]. Another thoroughly studied 3D perovskite, CsPbI 3 , demonstrates excellent thermal stability; however, it undergoes a phase change at room temperature to a form a large bandgap that is insufficient for absorbing UV radiation [ 4 ]. FAPbI 3 , on the other hand, also suffers from phase instability, as indicated by the presence of the yellow phase in the perovskite at room temperature [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been dedicated to analyzing the effect of mixed cations and halides to enhance PSCs’ stability and efficiency. Mixed cation perovskite is a unique way to benefit from the combined distinctive features of single cations: improved bandgap of perovskites with FA+ [ 9 ], impressive thermal stability with Cs+ [ 4 ], and high charge carrier mobility and long diffusion length with MA+ [ 5 , 10 , 11 ]. Incorporating MA cations with FA restricts the transition to the yellow non-perovskite phase by stabilizing the perovskite phase and enhancing the perovskite’s thermal and structural stability compared to the pure MA+ and FA+ cation 3D perovskite [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 29 ] The highest PCE for dopant‐free P3HT‐based all‐inorganic PSCs is just 14.08% although the devices show much improved ambient stability. [ 30 ] Recently, Seo and co‐workers reported that the wide‐bandgap interlayer could increase the open‐circuit voltage ( V oc ) and thus PCE for organic–inorganic hybrid PSCs. [ 31 ] Based on these facts, developing suitable methods to reduce the recombination in perovskite layer and suitable interlayer to alleviate the recombination at perovskite/P3HT interface would be effective to achieve high‐efficiency CsPbI 2 Br PSCs with dopant‐free P3HT HTM.…”
Section: Figurementioning
confidence: 99%